2017
DOI: 10.1063/1.4984262
|View full text |Cite
|
Sign up to set email alerts
|

Topologically nontrivial electronic states in CaSn3

Abstract: Based on the first-principles calculations, we theoretically propose topologically non-trivial states in a recently experimentally discovered superconducting material CaSn 3 . When the spin-orbit coupling (SOC) is ignored, the material is a host to three-dimensional topological nodal-line semimetal states. Drumhead like surface states protected by the coexistence of time-reversal and mirror symmetry emerge within the two-dimensional regions of the surface Brillouin zone connecting the nodal lines. When SOC is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 52 publications
1
21
0
Order By: Relevance
“…Up to now, the physical properties of ASn 3 have been less studied as compared with LnM 3 . The recent studies on CaSn 3 have revealed it as a weakly coupled type-II superconductor hosting eight pairs of WPs in the BZ with closed loops of surface Fermi arcs [47][48][49]. In light of the intriguing properties of CaSn 3 , investigation on the analogue BaSn 3 in terms of the electronic structure to examine possible nontrivial topological states is very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the physical properties of ASn 3 have been less studied as compared with LnM 3 . The recent studies on CaSn 3 have revealed it as a weakly coupled type-II superconductor hosting eight pairs of WPs in the BZ with closed loops of surface Fermi arcs [47][48][49]. In light of the intriguing properties of CaSn 3 , investigation on the analogue BaSn 3 in terms of the electronic structure to examine possible nontrivial topological states is very valuable.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we propose one of the simplest ways to realize a binary heavy element based on a closed-shell semiconductor with an alkaline earth element. 13,17,44,50,51 Investigations on Dirac materials are very interesting for quantum property studies. Similarly, studies of stanene functionalized films, 43,52 Nb 2 O 3 , 53 arsenene, 54 2D Mn-cyanogen, 55 and Bi/Sb (111) films 56 are in good agreement with previous studies.…”
Section: Results and Discussionmentioning
confidence: 99%
“…812 Contrarily, Dirac semimetals (DSMs) touch the Fermi level in the band structure calculation. 1317 The bulk band gap of nontrivial topology can be closed, and therefore, the energy level of the topologically protected metallic bulk states is critical in a topological quantum phase transition (TQPT). This has been enhanced by tuning an intrinsic material property such as SOC interaction by chemical doping or alloying of the composition.…”
Section: Introductionmentioning
confidence: 99%
“…When only T-symmetry is broken, the minimum number of pairs of Weyl points is one. There has been a massive effort devoted to investigating Weyl points and their associated phenomena in electronic systems, including Fermi arc surface states [72][73][74][75] and chiral anomalies [76][77][78][79][80][81]. Weyl points have also been found in photonic crystals [82][83][84][85][86][87][88], as well as acoustic [89,90] and plasmonic structures [91].…”
Section: B Weyl Pointsmentioning
confidence: 99%